Anticoagulation for mechanical aortic valves: An international survey of current practice patterns and perceptions - Saurabh Gupta; Charlotte C. McEwen; Winston Hou; Mark Crowther; Deborah Siegal; John Eikelboom; Richard P. Whitlock; Emilie P. Belley-Côté (Thrombosis Update, 2024)
Introduction: For patients with mechanical aortic valves, guideline recommended INR targets range from 2.0 to 3.5, depending on thromboembolic risk factors. Supporting data is largely historical and of low quality. We aimed to characterize clinicians’ practices around INR targets for these patients and perceptions of evidence supporting these recommendations. Methods: A 33-question web-based survey was sent to 75 cardiologists, cardiac surgeons, and thrombosis specialists globally. We inquired about anticoagulation practices for patients with mechanical aortic valves, perceptions of guideline recommendations, and interest in participating in a randomized controlled trial comparing lower and higher INR targets in these patients. Results: Of 55 respondents (73% response rate), 78% worked in academic hospitals. In patients with mechanical aortic valve and no additional thromboembolic risk factors, 80% targeted an INR of 2.5. Among patients with additional thromboembolic risk factors, 48% targeted an INR of 2.5, while 44% targeted an INR of 3.0. Additionally, 57% of respondents believed that evidence for the guidelines was up to date, and 53% believed that it applied to bi-leaflet valves.However, 57% of respondents said that the evidence was not high quality. Lastly, 66% of respondents would accept a higher thromboembolic risk to reduce risk of major bleeding; 86% were willing to randomize patients with mechanical aortic valve to a target INR of 2.0 if they had no thromboembolic risk factors. Conclusion: Clinicians target different INRs for patients with mechanical aortic valves; their perception of the evidence and guidelines varies. Of respondents, 86% would randomize patients to lower INR targets.